64, XX, SRY‐negative, Testicular DSD Syndrome in a Lusitano Horse. Issue 3 (12th October 2012) - Torres, A; Silva, JF; Bernardes, N; Sales Luís, J; Lopes da Costa, L
Contents Here is reported a disorder of sex development found in the Portuguese Lusitano horse breed. The complex genital phenotype included mammary glands, abdominal testes without epididymis, connected through oviducts to pelvic hypoplastic uterine horns and fused vulvar labia majora from which protruded ventrally a penis‐like structure. This structure was presented in a reversed position, the urethral opening placed dorsally in the glans. However, it was functional both for micturition and erection. The horse exhibited female micturition posture and aggressive male‐like behaviour, including flehmen, mounting, thrusting and flagging of the tail. Plasma testosterone concentrations were below detection limits and the genetic evaluation revealed a 64, XX, SRY‐negative karyotype. Surgery consisted in the removal of abdominal gonads followed by amputation of the penis and repositioning of the urethra. This case of reversion between the chromosomal and gonadal sex, associated with mixed anatomical and behavioural phenotype, illustrates that development of the testes may occur in the absence of the SRY gene and that other genetic and cellular pathways leading to gonad differentiation should be investigated.